2013
DOI: 10.1080/09540121.2013.825368
|View full text |Cite
|
Sign up to set email alerts
|

Positive parenting for positive parents: HIV/AIDS, poverty, caregiver depression, child behavior, and parenting in South Africa

Abstract: Families affected by HIV/AIDS in the developing world experience higher risks of psychosocial problems than non-affected families. Positive parenting behavior may buffer against the negative impact of child AIDS-orphanhood and caregiver AIDS-sickness on child wellbeing. Although there is substantial literature regarding the predictors of parenting behavior in Western populations, there is insufficient evidence on HIV/AIDS as a risk factor for poor parenting in low- and middle-income countries. This paper exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 62 publications
4
80
1
Order By: Relevance
“…Families with AIDS-ill caregivers or households with only one surviving parent often removed children from school if the main breadwinner was ill or deceased to earn money, which was consistent with Lachman et al (2013). 'I dropped out of school….…”
Section: Risk Factorsmentioning
confidence: 77%
“…Families with AIDS-ill caregivers or households with only one surviving parent often removed children from school if the main breadwinner was ill or deceased to earn money, which was consistent with Lachman et al (2013). 'I dropped out of school….…”
Section: Risk Factorsmentioning
confidence: 77%
“…However, the study does suggest that a parenting programme that is aimed at improving caregiver psychological health and encouraging positive parenting has the potential to safeguard against risks of poor child psychological and physical health outcomes in HIV-afected families living in poverty. This inding is promising that HIV-exposed caregivers have the ability to engage positively with their children, albeit, as the inding suggests, the efect size was small [31]. This nevertheless suggests, if adequately tailored interventions are implemented to look at strengthening the child-caregiver relationship, that it can ameliorate the children's response to the exposed adversities.…”
Section: Enhancing Resilience As a Protective Coping Mechanismmentioning
confidence: 96%
“…The beneit of interventions focusing on caregiver-child dyads has the potential to have a longlasting resilient efect on both children and their HIV-positive caregivers. Recently, the irst large study that examined the relationship between HIV/AIDS and positive parenting, using a sample of 2477 caregiver-child dyads, was conducted in KwaZulu-Natal [31]. Findings from the study indicated that HIV-positive caregivers and those caring for AIDS-orphaned children engaged in less positive parenting in comparison to non-afected families.…”
Section: Enhancing Resilience As a Protective Coping Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that families affected by a chronic disease have low family cohesion, report more isolation, and have more communication difficulties and more intrafamily conflicts compared to families where all members are healthy (Alderfer, Navsaria, & Kazak, 2009;Barakat, Lutz, Smith-Whitley, & Ohene-Frempong, 2005;Pai et al, 2007). Families affected by HIV distinguish themselves in terms of resiliency, social support, parentification (i.e., the adoption of parental roles by children), and the physical and emotional health of parents and children (Lachman, Cluvera, Boyesa, Kuob, & Casale, 2013;Lester et al, 2010;Li, Lin, Ji, Sun, & Rotheram-Borus, 2009;Murphy, Roberts, & Hoffman, 2002). Murphy, Herbeck, Marelich, and Schuster (2010) found that high levels of anxiety in mothers living with HIV (MLHIV) have a negative impact on their parenting skills.…”
Section: Introductionmentioning
confidence: 95%